Education and Learning from the Perspective of the Quran and Hadith - Irmawati; Andi Abd. Muis; Rusliana; Syamsuriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Education is an important foundation in the formation of individuals and societies with character. The Qur'an and Hadith provide comprehensive guidelines regarding the concept of education and learning, both in terms of objectives, methods, and implementation. This research aims to examine the perspective of education in the Qur'an and Hadith in order to provide a deep understanding of values that can be applied in the context of modern education. The method used is a literature study with a qualitative-descriptive approach. The results of the study show that education in Islam is not only oriented to the transfer of knowledge, but also the formation of morals and spirituality. This article provides insight into how the concept of education in Islam can be implemented in the contemporary education system. Education and learning have an important role in shaping the character of individuals and society. The perspective of the Quran and hadith provides fundamental guidance on the concepts, goals, and methods of ideal education. This study aims to examine the educational values in the Qur'an and hadith as well as their relevance to the context of modern learning. Using a qualitative-descriptive method, this study reveals that the principles of Islamic education are rooted in the values of monotheism, morals, and science. The results of the study show that the revelation-based learning approach can enrich contemporary educational practices, especially in building a generation with noble character and knowledge.